Rancang Bangun Prototype Robot Pengantar Barang Cargo Berbasis Arduino Mega Dengan IOT - Suyatmo Suyatmo; Catra Indra Cahyadi; Syafriwel Syafriwel; Rizaldy Khair; Iswandi Idris (Universitas Budi Darma, 2020)
Cargo is the goods transported by ship, aircraft or other types of transportation. Cargo is divided into three types of transportation, namely, air, land and sea. Cargo service is a special service for transporting goods using aircraft. This service can be organized by a regular airline that serves passengers, but can also be carried out by a specialized airline freight company. With the development of industrial automation technology, robots are needed to help meet their needs quickly. With this developed robotics technology to help alleviate human work in the future. Goods delivery robot is a robot created to help work in delivering goods to aircraft cargo. This robot can stuff automatically. This goods transfer robot uses the Internet of Things method that is already connected to a smartphone remote control based on an android application. Writing program code using Arduino IDE 1.8.9 and using Android as a robot control. This robot uses 4 channel line tracker sensors, 2 DC motors and motor drivers as controllers, Arduino uno as the brain in this robot system. The results of this study produce a prototype robot that can deliver goods into aircraft cargo in airports.